Differences in the composition of the bacterial element of the urinary tract microbiome in patients undergoing dialysis and patients after kidney transplantation - Jaworska, Marcelina M.; Pecyna, Paulina; Jaskiewicz, Katarzyna; Rydzanicz, Małgorzata; Kaluzna, Malgorzata; Pawlaczyk, Krzysztof; Ploski, Rafal; Nowak-Malczewska, Dorota M.; Karolak, Justyna A.; Gajecka, Marzena (Frontiers in Microbiology, 2023)
The development of molecular biology methods and their application in microbial research al-lowed the detection of many new pathogens that cause urinary tract infections (UTIs). Despite the advances of using new research techniques, the etiopathogenesis of UTIs, especially in patients un-dergoing dialysis and patients after kidney transplantation, is still not fully understood. This study aimed to characterize and compare the composition of the bacterial element of the urinary tract microbiome between the groups of patients undergoing dialysis (n=50) and patients after kidney transplantation (n=50), with positive or negative urine culture, compared to controls (n=50). Significant bacteriuria was observed in 30% of the urine cultures of patients undergoing dial-ysis and patients after kidney transplantation, with Escherichia coli as the most dominant microor-ganism (73%) detected with the use of classical microbiology techniques. However, differences in the bacterial composition of the urine samples between the evaluated patient groups were demonstrated using the amplicon sequencing. Finegoldia, Leptotrichia, and Corynebacterium were found to be discriminative bacteria genera in patients after dialysis and kidney transplantation compared to individuals without urinary tract dysfunction. In addition, in all of urine samples, including those without bacteriuria in classical urine culture, many types of bacteria have been identified using 16S rRNA sequencing. The revealed microbial characteristics may form the basis in searching for new diagnostic markers in in treatment of patients undergoing dialysis and patients after kidney transplan-tation.